Religiusitas Sebagai Moderator Hubungan Kecemburuan dan Kualitas Hubungan Perempuan dengan Pasangan - Hasanah, Uswatun (Jurnal Konseling dan Psikologi Indonesia, 2025)
The quality of an individual's relationship with a partner is an important aspect of an individual's life and it can be caused by jealousy. The results of previous studies found inconsistencies in the impact of jealousy on the quality of relationships, especially in women. While the quality of individual relationships with partners can be improved by religiosity. This study aims to determine the relationship between jealousy and the quality of women's relationships with partners, also the role of religiosity as a moderator. This research is a quantitative study with 160 participants who are married and living in Sampang. Measuring instruments used are The Positive Relationship Quality (PRQ) Scale, Multy Dimensional Jealousy Scale (MJS), dan Centrality of Religiosity Scale (CRS) and analyzed using a Process Macro. This research results showed that high jealousy caused the low quality of the relationship and religiosity can reduce jealousy effect on the quality of the relationship between women and partners.